Institutional trust in the time of corona: Evidence from countermeasures in Germany - Wolfgang Stojetz; Neil T. N. Ferguson; Ghassan Baliki; Sarah Fenzl; Patricia Justino; Tilman Brück (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
We study how the stringency of policy measures to counter the COVID-19 pandemic affects individuals' trust in formal institutions. Drawing on micro-level panel data from Germany spanning an 18-month period from the onset of the pandemic, we show that, on average, there is a pronounced negative relationship between the stringency level of COVID-19 countermeasures and trust in institutions. We present empirical evidence to argue that the underlying mechanism is a perceived illegitimate attack on civil liberties, reducing trust in the judiciary in particular. This effect is concentrated in the period from October 2020, six months into the pandemic, when stringency measures in Germany started to increase again. For the early stage of the pandemic, we present evidence for competing, positive impacts of stringency responses on trust in government, consistent with other studies of pandemic onset, resulting in no significant net impact on institutional trust in that stage. In consequence, our findings suggest that hard lockdown measures beyond the initial stage of a pandemic are highly detrimental for institutional trust.
Keywords: D02; H12; I18; R28; 330; COVID-19; coronavirus; pandemic; crisis; survey data; trust; institutions